Managing competitive advantage: Clustering in the Singapore financial centre - Adrian T.H. Kuah (The University of Manchester, Manchester Business School, 2008)
This article uncovers the role of financial clustering in creating competitive advantage for incumbents in the Singapore Financial Centre. The revelatory case of the underresearched Singapore cluster reveals (a) how clustering conditions have influenced the development of the City as a financial centre, (b) how the conditions can be defined for a cluster in a small and open economy, and (c) whether there could be a generalisation of the concept to a global services cluster. The Porterian Diamond is found to be an effective tool to tease out the characteristics that result in many tangible and intangible benefits that industry players find important. The article concludes with the strategic and managerial implications to suggest the three golden rules that a location can help firms optimise on these benefits in attaining international competitiveness.
Keywords: 330; financial services; international competitiveness; diamond; clusters; Singapore; Wettbewerbsvorteil; Clusteranalyse; Finanzplatz; Kleines-offenes-Land; Singapur